THE IMPACT OF DIGITAL MARKETING AND E-MONEY ON MSME SALES IN THE FASHION SECTOR: A CASE STUDY IN SIDOARJO - Sasa Mulyanti; Nihlatul Qudus Sukma Nirwana (Antis Publisher, 2025)
Objective: This study aims to determine the Influence of Digital Marketing and the Use of E-Money on the Sales Volume of Micro, Small and Medium Enterprises (MSMEs) in the Fashion Sector (Empirical Study on MSMEs in Sidoarjo District). Method: This study uses a quantitative method with primary data as a data source. The population in this study is fashion MSMEs in Sidoarjo in 2023. The method used in determining this sample is using the Random sampling method. The number of samples used in this study was 39 respondents. The data analysis technique used in this study was SPSS Version 27. Results: The results of this study indicate that Digital Marketing Affects the Sales Volume of Micro, Small and Medium Enterprises (MSMEs) in the Fashion Sector in Sidoarjo City. The Use of E-Money Affects the Sales Volume of Micro, Small and Medium Enterprises (MSMEs) in the Fashion Sector in Sidoarjo City. Novelty: This study provides empirical evidence on the simultaneous influence of Digital Marketing and E-Money usage on sales volume specifically within fashion MSMEs in Sidoarjo, which has not been extensively studied before.